Mitral Valve Stenosis after Open Repair Surgery for Non-rheumatic Mitral Valve Regurgitation: A Review - Shabsigh, Muhammad; Lawrence, Cassidy; Rosero-Britton, Byron R.; Kumar, Nicolas; Kimura, Satoshi; Durda, Michael Andrew; Essandoh, Michael (Frontiers in Cardiovascular Medicine, 2016)
Mitral stenosis (MS) after mitral valve repair is a slowly progressive condition, usually detected many years after the index mitral valve surgery. It is defined as a transmitral pressure gradient (TMPG) of >5 mmHg or a mitral valve area (MVA) <1.5 cm2. Pannus formation around the valve annulus or extending to the valve leaflets is suggested as the main mechanism for developing delayed MS after MV repair. Early stenosis, on the other hand, is thought to be a direct result of an undersized annuloplasty ring. Furthermore, in MS following ischemic mitral regurgitation (MR), subvalvular tethering is the hypothesized pathophysiology. MS after MV repair has an incidence of 9-54%. Several factors are associated with higher risk for developing MS after mitral valve repair including; flexible Duran annuloplasty rings versus rigid Carpentier-Edwards (CE) rings, complete annuloplasty rings versus partial bands, smaller anterior leaflet opening angle and anterior leaflet tip opening length. Intraoperative echocardiography can measure the MVA and TMPG values that have been suggested as possible predictors of future development of MS.